2006
DOI: 10.1007/s10661-006-7231-3
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Lakes in Finland: Current Water Quality and Trends

Abstract: Agriculture is the largest source of nutrients into surface waters in Finland, and yet relatively little is known about the actual impact of the agricultural load on the state of lakes. We analysed the water quality data of 20 Finnish agricultural lakes and found that they had higher levels of nutrients, chlorophyll a and turbidity than did the other types of lakes (e.g. those receiving point-source load) in the national monitoring network (the Finnish Eurowaternet). Currently, six of the agricultural lakes ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 31 publications
2
28
0
1
Order By: Relevance
“…As several studies provided more information on the type of agriculture, we know that at least a few regions were dominated by pastureland (namely Galbraith and Burns 2007; Chen and others 2008; Prairie and Parkes unpublished), whereas others were predominantly cropland (namely Arbuckle and Downing 2001;Vander Zanden and others 2005;Ekholm and Mitikka 2006). Given this variability in agricultural land-use practices and in the data ranges represented across studies, we, not surprisingly, found a broad spectrum of correlation coefficients (r = 0.15-0.86) when the TP-% Agr relationship was assessed with linear correlation for each study individually (Table 1).…”
Section: Variation In Water Quality Agriculture and Lake Depth Acromentioning
confidence: 99%
See 1 more Smart Citation
“…As several studies provided more information on the type of agriculture, we know that at least a few regions were dominated by pastureland (namely Galbraith and Burns 2007; Chen and others 2008; Prairie and Parkes unpublished), whereas others were predominantly cropland (namely Arbuckle and Downing 2001;Vander Zanden and others 2005;Ekholm and Mitikka 2006). Given this variability in agricultural land-use practices and in the data ranges represented across studies, we, not surprisingly, found a broad spectrum of correlation coefficients (r = 0.15-0.86) when the TP-% Agr relationship was assessed with linear correlation for each study individually (Table 1).…”
Section: Variation In Water Quality Agriculture and Lake Depth Acromentioning
confidence: 99%
“…The mixed-effects estimates are often referred to as shrinkage estimates as they 'shrink' the individual OLS estimates toward the common population estimate, providing robustness to individual outlying behavior (Pinheiro and Bates 2004). The shrinkage toward the common term is particularly noticeable in the Finnish dataset (Figure 2; Ekholm and Mitikka 2006).…”
Section: Mixed Effects Models: Variability In the Correlative Relatiomentioning
confidence: 99%
“…A possible reason is the different quality of water bodies in different landscapes. Lakes in agricultural landscapes tend to be more eutrophic, as intensive agriculture is usually the primary source of nutrients in surface waters (Mehner et al 2005;Ekholm and Mitikka 2006;Schindler et al 2006). The higher productivity in eutrophic lakes has been related to the population increase of several waterfowl species (Suter 1995;Fernandez et al 2005).…”
Section: Shifting Distribution Of the Expanding Populationmentioning
confidence: 99%
“…The 20 lakes studied are listed in Table 2 and have been described in detail by Ekholm and Mitikka (2006). Their size ranged from 0.4 to 155 km 2 and their maximum depth from 1.7 to 68 m. The majority did not undergo thermal stratification in summer.…”
Section: Study Sitesmentioning
confidence: 99%
“…Recent assessments of agricultural impacts on aquatic systems showed no clear reduction in either nutrient loading or eutrophication (Mitikka and Ekholm 2003, Räike et al 2003, Ekholm and Mitikka 2006. This may partly be explained by the lag period between the measures taken and the desired outcome due to the large nutrient reserves accumulated in the soil (Stålnacke et al 2003.…”
Section: Introductionmentioning
confidence: 99%